2005
DOI: 10.1074/jbc.m411694200
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Gene Knockout Male Mice Exhibit Impaired Cardiac Growth and Exacerbation of Angiotensin II-induced Cardiac Fibrosis

Abstract: Androgen has anabolic effects on cardiac myocytes and has been shown to enhance left ventricular enlargement and function. However, the physiological and patho-physiological roles of androgen in cardiac growth and cardiac stress-induced remodeling remains unclear. We aimed to clarify whether the androgen-nuclear androgen receptor (AR) system contributes to the cardiac growth and angiotensin II (Ang II)-stimulated cardiac remodeling by using systemic AR-null male mice. AR knock-out (ARKO) male mice, at 25 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 53 publications
(53 reference statements)
4
99
0
2
Order By: Relevance
“…Cameron et al demonstrated that BMK1 activation attenuates the cardiac injury which occurs after myocardial ischemia and reperfusion (47). Additionally, we have recently reported that cardiac BMK1 is significantly activated in angiotensin II-stimulated mice exhibiting cardiac hypertrophy and fibrosis (5). All of these reports support the suggestion that BMK1 activation might be one of the signs of the progression of cardiac diseases.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Cameron et al demonstrated that BMK1 activation attenuates the cardiac injury which occurs after myocardial ischemia and reperfusion (47). Additionally, we have recently reported that cardiac BMK1 is significantly activated in angiotensin II-stimulated mice exhibiting cardiac hypertrophy and fibrosis (5). All of these reports support the suggestion that BMK1 activation might be one of the signs of the progression of cardiac diseases.…”
Section: Discussionsupporting
confidence: 77%
“…30 (2007) No.11 p.1107No.11 p. -1117 Original , Masanori YOSHIZUMI 2) , Keisuke ISHIZAWA 1) , Yoshiko FUJITA 1) , Shuji KONDO 3) , Shoji KAGAMI 3) , Kazuyoshi KAWAZOE 4) , Koichiro TSUCHIYA 1) , Shuhei TOMITA 5) , and Toshiaki TAMAKI …”
Section: Hypertens Resunclassified
“…The left atrium was detected in the parasternal long axis view at the aortic root and measured in the systole phase at its maximal dimension during M-mode images. The methods of measurements in left ventricular dimension and left ventricular fractional shortening (%FS) calculation were described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…cDNA Synthesis and Quantitative Real Time PCR-Atria and ventricular tissue were homogenized in TRIzol reagent, and RNA was extracted as described previously (17). A QuantiTect Reverse Transcription kit (Qiagen, Valencia, CA) was used to synthesize cDNA, and PCR was performed using the iCycler iQ Real Time PCR Detection Systems (Bio-Rad) with SYBR Green dye (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation